(3VhA GdTgGHs - (3CHhGdeXaQ eMeO Hf CSYO GdeYQha HGHf GdMcjes; (3GdbVGYj , TgGH GdOjf CHh YHO Gddg eMeO Hf SdGeI Hf LYaQ Hf Ydj Hf Mcehf GdbVGYj,J (B454 (3g` s
(3ChdgG (B:s
(3ef def JZf HGdbQBf adjS efG Cj ef de jSJZf Hg hjbJHS ef fhQg hdGojQjO Hg GdZfGA hJQLjY GdUhJ s
(3BNQgG (B:s
(3hGdbdH GdPj dGjNTY cGdUNQI GdJj dGJdjf dG EYJHGQ HgG s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B42 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B71s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1067s
Keywords: (3GdMOjK h GdeUWdMs